Diplopia as the Complication of Cataract Surgery - Maciej Gawęcki; Andrzej Grzybowski (Journal of Ophthalmology, 2016)
The authors present systematic review of aetiology and treatment of diplopia related to cataract surgery. The problem is set in the modern perspective of changing cataract surgery. Actual incidence is discussed as well as various modalities of therapeutic options. The authors provide the guidance for the contemporary cataract surgeon, when to expect potential problem in ocular motility after cataract surgery.